Interactive effect of intercropping systems and fertility levels on yield and economics of summer cowpea intensified with baby corn - Anju Bijarnia; J.P. Tetarwal; Baldev Ram; Pratap Singh; Rajendra Yadav; Anil Kumar Gupta (Annals of Agricultural Research, 2022)
An experiment was conducted during Summer season of 2019 and 2020 at Agricultural Research Station, Agriculture University, Kota, Rajasthan, India to study the interactive effect of intercropping systems and fertility levels on yield and economics of summer cowpea intensified with baby corn. There are thirty treatment combination with five intercropping systems [sole cowpea, sole baby corn, cowpea + baby corn (2:1), cowpea + baby corn (3:1) and cowpea+ baby corn (4:1)] in main plot, three fertility levels (100, 125 and 150% RDF) in sub plot and two stress mitigating chemicals (0.5% CaCl2 and 1% KNO3 at flowering and pod development stage of cowpea) in sub-sub plot and replicated four time. Interactive effect was exists within the intercropping systems and fertility levels. Data showed that the significantly higher cowpea equivalent yield gross returns, net returns and B:C ratio was recorded in cowpea and baby corn 2:1 row ratio fertilized with 150% RDF over rest of the treatment combinations.